Critique de livre : TERRY WOTHERSPOON. The Sociology of Education in Canada. Critical Perspectives. (2014). - Leblanc, Dominic (McGill Journal of Education / Revue des sciences de l'éducation de McGill, 2018)
TERRY WOTHERSPOON. The Sociology of Education in Canada. Critical Perspectives (4e éd.). Toronto, ON : Oxford University Press. (2014). 372 p. 79,95 $ (édition de poche) (ISBN 978-0-19-544548-0)